Rancang Bangun Aplikasi Pelaporan Koperasi Wanita Bhakti Ibu Kota Malang - Laksmana, Dimas Indra; Rahman, Nanik Astuti; Hudha, Muhammad Istnaeny; Minah, Faidliyah Nilna (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2018)
Statute Cooperative and Koperasi Wanita Bhakti Ibu is prepare accountability report, as well as submission of work plan and budget plan of expenditure of cooperative expenditure at Rapat Anggota Tahunan (RAT) Forum. Presentation of accountability report in RAT which is a forum for sharing is expected to give member's opportunity to objectively and constructively assess the existence and development of cooperative as a whole, in the field of organization, management, capital, business and other activities. The latest financial reports, therefore need improvement and innovation by creating a computerized reporting application to simplify and mitigate work and minimize errors in reporting figures. Research method used to analyze system on Koperasi and design system to cooperative. System analysis purpose is tobe able identify and evaluate problems that occur and expected needs, so it can be proposed improvement. After build application, resulted conclusions: (1) Based on trial, application run effectively, minimize errors in performing data storage and facilitate data search and transactions more quickly and accurately; (2) Based on trial, application capable reports of transaction or financial administration, according to user current desire.